Thermal behavior of myofibrillar proteins from the adductor muscles of scallops : A differential scanning calorimetric study (DSC) - Paredi, María Élida (2003)
Muscles and different proteins obtained from scallops (Chlamys tehuelchus and Zygochlamys patagonica) were analyzed. In both species of scallop, the thermograms of striated and smooth muscles showed two endothermic transitions. The T max values corresponding to striated and smooth muscles from C. tehuelchus were 53.2, 79.0°C and 52.7, 78.0°C, respectively. The T max corresponding to striated and smooth muscles of Z. patagonica were 55.0, 79.2°C and 54.7, 78.7°C, respectively. No significant differences were observed between the thermal transitions of myofibrils and actomyosin of both types of muscles from both species of scallop. Irrespective of the species, the thermal stability decreased when the pH of the muscles was increased. The increase in ionic strength greatly affected T max, the ΔH total and the ΔH of the first transition. A significant decrease in ΔH total and ΔH corresponding to both transitions was observed, particularly in the striated muscles of Zygochlamys patagonica. These results indicate a major sensitivity of the adductor muscles of Zygochlamys to changes in the chemical environment.